2003
DOI: 10.1159/000070656
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of hCG Receptor mRNA in Four Human Ovarian Cancer Cell Lines Varies Considerably under Different Experimental Conditions

Abstract: In the present study, expression and regulation of hCG receptor mRNA were analyzed in four established human ovarian cancer cell lines using different concentrations of hCG, EGF, and 8-bromo-cAMP for different periods between 6 and 72 h. The cells were examined for the hCG receptor using the reverse-transcriptase polymerase chain reaction with specific primers amplifying the hCG receptor gene. Receptor mRNA was found in all cell lines. In the line OVCAR-3, it was expressed in all samples independent of kind an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Earlier it was shown by others that OVCAR-3 cells express the LH / hCG receptor [10] . However, this cell line was not known expressing the ANG2 gene.…”
Section: Results ▼mentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier it was shown by others that OVCAR-3 cells express the LH / hCG receptor [10] . However, this cell line was not known expressing the ANG2 gene.…”
Section: Results ▼mentioning
confidence: 96%
“…We therefore cloned promoter fragments of the ANG2 regulatory region into luciferase reporter constructs, transfected these constructs in the human ovarian cancer cell line OVCAR-3, and analyzed the expression ratio before and after hCG stimulation. This cell line was shown to be a target of hCG regulated LH-receptor expression levels [10] and of hCG guided reduction of tumor volume and burden in animal models [11] .…”
Section: Introduction ▼mentioning
confidence: 99%
“…In particular, alternative splicing appears to be associated with cycle-dependent regulation of LHR mRNA levels in human endometrium [21] and receptor down-regulation in rat corpora lutea [17]. In addition, the different types of splice variants have also been shown to take place in pathophysiological conditions, such as endometrial carcinomas, which is related to increased levels of spliced LHR transcripts [22] or in human ovarian [31,36] and breast epithelial cell tumors [15], in which alternative splicing is shown to be altered or ceased when compared to normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such a regulatory role could be assigned to other splice variants of the LHR in general is not known. However, this is a very likely possibility, because changes in physiological stimuli (Lakkakorpi et al, 1993;Licht et al, 2003), cellular differentiation (Sokka et al, 1992;Tena-Sempere et al, 1994;Zhang et al, 1994;Apaja et al, 2004Apaja et al, , 2005 and tumorigenic cell growth (Lin et al, 1994;Reinholz et al, 2000;Jiang et al, 2002;Steinmeyer et al, 2003) have all been shown to regulate the splicing pattern of the receptor.…”
Section: Discussionmentioning
confidence: 99%